Bio-inspired materials to control and minimise insect attachment. (1st September 2022) - Bergmann, Johannes B; Moatsou, Dafni; Steiner, Ullrich; Wilts, Bodo D
Abstract: More than three quarters of all animal species on Earth are insects, successfully inhabiting most ecosystems on the planet. Due to their opulence, insects provide the backbone of many biological processes, but also inflict adverse impacts on agricultural and stored products, buildings and human health. To countermeasure insect pests, the interactions of these animals with their surroundings have to be fully understood. This review focuses on the various forms of insect attachment, natural surfaces that have evolved to counter insect adhesion, and particularly features recently developed synthetic bio-inspired solutions. These bio-inspired solutions often enhance the variety of applicable mechanisms observed in nature and open paths for improved technological solutions that are needed in a changing global society.